'We did not come here as tenants, but as landlords': Nigerian Pentecostals and the power of maps - Knibbe, Kim E. (African Diaspora, 2009)
This article is an attempt to show how the spaces in which African Christians in Amsterdam can move are produced by the mapping of various actors and the geographies that are created based on these maps. It fi rst situates and describes a Nigerian-initiated Pentecostal church within global cultural flows, in relation to Nigeria and in relation to the Netherlands. In the view of many African Pentecostals, Europe, and by extension the Netherlands and Amsterdam, are territories which should be won back for Jesus. Subsequently, I show how 'producing the local' is crucially important to the goals of this church and how this relates to mapping and the production of religious geographies. The last part of this paper analyses how one particular location of this church, namely the South East of Amsterdam, shows up on a very diff erent map that pinpoints this neighbourhood as a centre of Nigerian crime. In both cases, maps turn out to be a powerful means to mobilise money and people to produce long-lasting results. © Koninklijke Brill NV, 2009.
Paid
Keywords: Geographies; Mapping; Nigerian crime; Producing the local; Redeemed Christian Church of God